Health research in the Syrian conflict: opportunities for equitable and multidisciplinary collaboration. (21st May 2021) - Ekzayez, Abdulkarim; Olabi, Amina; Douedari, Yazan; Meagher, Kristen; Bowsher, Gemma; Farhat, Bashar; Patel, Preeti
Abstract: There is considerable global momentum from Syrian researchers, policy makers and diaspora to address health, security and development challenges posed by almost a decade of armed conflict and complex geopolitics that has resulted in different areas of political control. However, research funders have been so far reluctant to invest in large-scale research programmes in severely conflict-affected areas such as northern Syria. This paper presents examples of collaborations and programmes that could change this through equitable partnerships between academic and operational humanitarian organizations involving local Syrian researchers—a tremendous way forward to capitalize and accelerate this global momentum. Several academic and humanitarian organizations have initiated collaborations to build new networks and partnerships for better research and policy engagement in Syria. The networks conducted two consecutive annual conferences in 2019 and 2020. Key messages from these conference include: (1) equitable partnerships between organizations and individual researchers must form the basis of conducting better research; (2) ensuring the inclusion of local Syrian researchers is crucial in the development of any viable partnership; (3) capacity strengthening in health research is urgently needed in Syria's current phase of active conflict to inform, develop and implement strengthened and sustainable health systems in the post-conflict phase.